2003
DOI: 10.1161/01.hyp.0000044938.94050.e3
|View full text |Cite|
|
Sign up to set email alerts
|

Antihypertensive Treatments Obscure Familial Contributions to Blood Pressure Variation

Abstract: Abstract-The linkage and association between inherent blood pressure and underlying genotype is potentially confounded by antihypertensive treatment. We estimated blood pressure variance components (genetic, shared environmental, individual-specific) in 767 adult volunteer families by using a variety of approaches to adjusting blood pressure of the 244 subjects (8.2%) receiving antihypertensive medications. The additive genetic component of variance for systolic pressure was 73.9 mm Hg 2 (SE, 8.8) when measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
229
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 248 publications
(232 citation statements)
references
References 19 publications
3
229
0
Order By: Relevance
“…We adjusted for age and HUNT survey occasion, which should reduce the potential impact that secular trends in blood pressure,44 BMI,45 waist circumference,46 and cholesterol47 during our study period may have had on the observed difference between HDP and normotensive women. Antihypertensive treatment was used more frequently in women with a history of HDP, and although we attempted to remedy this by adding constants to the observed blood pressure measurements, as recommended by Cui et al26 and Tobin et al,27 antihypertensive use could have lowered blood pressure in HDP more than in normotensive women and attenuated the estimated difference between the groups. The use of statin treatment has increased substantially in Norway starting in the late 1990s48 and could have lowered non‐HDL cholesterol levels in women attending HUNT3 (2006–2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We adjusted for age and HUNT survey occasion, which should reduce the potential impact that secular trends in blood pressure,44 BMI,45 waist circumference,46 and cholesterol47 during our study period may have had on the observed difference between HDP and normotensive women. Antihypertensive treatment was used more frequently in women with a history of HDP, and although we attempted to remedy this by adding constants to the observed blood pressure measurements, as recommended by Cui et al26 and Tobin et al,27 antihypertensive use could have lowered blood pressure in HDP more than in normotensive women and attenuated the estimated difference between the groups. The use of statin treatment has increased substantially in Norway starting in the late 1990s48 and could have lowered non‐HDL cholesterol levels in women attending HUNT3 (2006–2008).…”
Section: Discussionmentioning
confidence: 99%
“…We used the mean of the second and third measurement, except for 2135 women in HUNT3 who lacked the third measurement because of sick leave among staff; for them, we used the second measurement only. Based on recommendations by Cui et al26 and Tobin et al,27 we added 10 mm Hg to systolic and 5 mm Hg to diastolic blood pressure levels for 2137 women who reported taking antihypertensive medication. We classified women as having hypertension if they reported taking antihypertensive medication, or whose blood pressure was either ≥140 mm Hg systolic or ≥90 mm Hg diastolic.…”
Section: Methodsmentioning
confidence: 99%
“…Normotensive patients receiving vasodilators for RP may have falsely lower blood pressure readings. To capture the full effects of blood pressure on the CACS, we replaced hypertension with adjusted systolic or diastolic blood pressure in the logistic regression model and adjusted for the blood pressure-lowering effects of vasodilator therapy by adding 10 mm Hg and 5 mm Hg to the systolic and diastolic blood pressure readings, respectively, according to the method of Cui et al (26) for patients receiving vasodilators, regardless of the indication. SSc remained a highly significant independent risk factor for increased coronary calcification.…”
Section: Discussionmentioning
confidence: 99%
“…10 This adjustment has been included to account for the average response to therapy and is supported by previous family studies. 11 We also used categorical classifications (hypertensive or normotensive) to assess the odds ratios (OR) for hypertension in the admixed populations. For these assessments, we used the following definitions: (1) In addition, we also performed analyses in which individuals that met either diastolic or systolic definitions were classified as hypertensive and individuals meeting both diastolic and systolic definitions for the normal range were classified as normotensive.…”
Section: Study Subjectsmentioning
confidence: 99%